2021
DOI: 10.1093/eurheartj/ehab724.3228
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular localization of AMP deaminase and its novel role in BCAA and lipid metabolism in diabetic cardiomyopathy

Abstract: Background A metabolomic study in the human heart suggested a pivotal role of amino acid (AA) metabolism in fatty acid oxidation, which is dysregulated in type 2 diabetes mellitus (T2DM) and heart failure. We previously reported that aberrant up-regulation of AMP deaminase 3 (AMPD3) impairs cardiac energetics in T2DM hearts, and AMPD3 was recently shown to be activated by fasting and to promote AA metabolism and fatty acid oxidation in skeletal muscle. A sodium glucose cotransporter 2 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In addition, AMPD3 in erythrocytes catalyzes AMP into IMP if AMPD3 is overexpressed, and it accelerates these biochemical reactions and lowers AMP levels. Previous studies of the obese rat model of T2D have shown that the upregulated protein levels of AMPD3 could impair cardiac energy by targeting ATP depletion and systolic dysfunction (Tatekoshi et al, 2018;Igaki et al, 2021;Ogawa et al, 2023). In this study, the results in the online datasets were consistent with previous studies that the AMPD3 gene was upregulated in T2D samples.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, AMPD3 in erythrocytes catalyzes AMP into IMP if AMPD3 is overexpressed, and it accelerates these biochemical reactions and lowers AMP levels. Previous studies of the obese rat model of T2D have shown that the upregulated protein levels of AMPD3 could impair cardiac energy by targeting ATP depletion and systolic dysfunction (Tatekoshi et al, 2018;Igaki et al, 2021;Ogawa et al, 2023). In this study, the results in the online datasets were consistent with previous studies that the AMPD3 gene was upregulated in T2D samples.…”
Section: Discussionsupporting
confidence: 91%
“… 311 They play critical roles in biological pathways and serve as valuable bioindicators during cellular processes. 91 , 312 , 313 Metabolic profile could provide a snapshot of complex interplay between environment and intermediary processes. 314 316 Once specific metabolites to disease pathophysiology are identified and then gain interest in understanding biological biomarkers within mechanistic pathways, using an invasive approach to monitor disease progression and distinguish diseased subjects.…”
Section: Identification Of Bioactive Metabolitesmentioning
confidence: 99%